Laser tracker orientation in confined space using on-board targets. (7th July 2016) - Gao, Yang; Kyle, Stephen; Lin, Jiarui; Yang, Linghui; Ren, Yu; Zhu, Jigui
Abstract: This paper presents a novel orientation method for two laser trackers using on-board targets attached to the tracker head and rotating with it. The technique extends an existing method developed for theodolite intersection systems which are now rarely used. This method requires only a very narrow space along the baseline between the instrument heads, in order to establish the orientation relationship. This has potential application in environments where space is restricted. The orientation parameters can be calculated by means of two-face reciprocal measurements to the on-board targets, and measurements to a common point close to the baseline. An accurate model is then applied which can be solved through nonlinear optimization. Experimental comparison has been made with the conventional orientation method, which is based on measurements to common intersection points located off the baseline. This requires more space and the comparison has demonstrated the feasibility of the more compact technique presented here. Physical setup and testing suggest that the method is practical. Uncertainties estimated by simulation indicate good performance in terms of measurement quality.